The welfare state in Britain since 1945 - Lowe, Rodney (Palgrave Macmillan, 2005)
An historical account of welfare policy in postwar Britain, tracing the development of policy through the period of "consensus" between 1945 and 1975 and then the years between 1976 and 1990, when state welfare came under ideological attack. An assessment is made of the relative successes and failures of each area of policy: employment policy, social security, the National Health Service, education, housing, and the personal social services. Acidic paper